Topical Application of Exosomes in a Patient with Acne Conglobata: A Case Report - Handayani, Theressia; Luziani, Stefani (UI Scholars Hub, 2025)
Background: Acne conglobata (AC) is a rare and severe acne characterized by interconnected nodules, cysts, and abscesses. Mesenchymal stem cell-derived exosomes (MSC-exosomes) have immunosuppressive properties that alleviate inflammation and immunological reactions. We present a case of AC in a patient who received topical administration of exosomes. Case Illustration: A 20-year-old male was diagnosed with AC, presenting as inflammatory papules and cysts covered with yellowish crusts that had been present for five months. Exosomes (ASCE+®, Seoul, South Korea) were topically administered at a dose of 5 mL, applied evenly to the face. The patient underwent three treatment sessions, with a one-week interval between sessions. Photographic images were captured before treatment, immediately after the final session, followed by one week and then three weeks after the final treatment session. The patient expressed complete satisfaction with the implemented treatment and disclosed no adverse effects. Discussion: The present case report illustrates the therapeutic advantages associated with the use of exosomes in a patient with AC. The therapeutic targeting of inflammatory regulators is crucial in treating AC. Studies have shown that MSCs possess inherent immunosuppressive properties that can help alleviate inflammation and immunological reactions. MSC-exosomes offer additional benefits, including angiogenic capacity and collagen synthesis. The study's limitations include the short follow-up duration and the lack of a control group. Conclusion: Exosomes have the potential to serve as cosmeceutical in the treatment of AC, due to their anti-inflammatory, regenerative, and antimicrobial properties.